The impact of prebiotics, probiotics and synbiotics on the prevention and treatment of atopic dermatitis in children: an umbrella meta-analysis - Wang, Lifeng; Xu, Lijuan (Frontiers in Pediatrics, 2025)
BackgroundStudies have suggested that the administration of prebiotics, probiotics and synbiotics (pre-, pro-, and synbiotics) may potentially decrease the incidence of atopic dermatitis (AD) and alleviate its severity in children; however, recent studies have yielded inconclusive findings.ObjectiveThis umbrella meta-analysis aimed to comprehensively assess the effect of pre-, pro-, and synbiotics on AD among children.MethodsA systematic search was carried out in the PubMed and Scopus databases up to April 2024 to identify relevant meta-analyses. Relative risks (RR) and weighted mean differences (WMD) along with their 95% confidence intervals (CI) were pooled using a random effects model to evaluate the impacts on both the incidence of AD and its severity, as assessed by the Scoring Atopic Dermatitis (SCORAD) index.ResultsThis umbrella meta-analysis included 38 meta-analyses, with 127,150 participants. The analysis suggested that intervention with pre-, pro-, and synbiotics significantly reduced the incidence of AD (RR = 0.74, 95% CI: 0.70–0.79), which was confirmed by subgroup analyses. The treatment significantly reduced SCORAD score (WMD = −3.75, 95% CI: −5.08 to −2.42). In subgroup analysis, multi-strain probiotics, Lactobacillus, synbiotics, and pre-, pro-, and synbiotics mixtures were found to significantly decrease the SCORAD score, while, Bifidobacterium and prebiotics alone did not show a significant effect on the SCORAD score. The treatment resulted in a significant decrease in SCORAD score among children with moderate to severe AD, but not in subjects with mild AD.ConclusionsProbiotics and synbiotics could be promising interventions to reduce the risk of developing AD and alleviate its severity in children.